Occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand indicate biodiversity change - Irene Middleton; Malcolm Francis; J. David Aguirre; Carl Struthers; Thomas Trnski; Clinton Duffy; John Anderson; Mary Carney; Nathan Cox; Stephen Hemstalk; Blair Herbert; Craig Johnston; et al. (Journal of Biogeography, 2023)
Aim Climate change is driving biogeographic change globally, including poleward range shifts of species and the increasing abundance of rare species. We examine spatiotemporal patterns in the occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand to determine whether biodiversity change is occurring in this temperate region and to set a baseline for future monitoring of climate change impacts. Location Aotearoa New Zealand (NZ). Taxon Marine fishes. Methods We consolidated 100 years of unpublished records and citizen science sightings of tropical, subtropical and rare fishes to develop a focal species database for NZ. Using hotspot analysis, we identified geographic locations where the occurrence and diversity of focal species is greater than expected. We examine the spatiotemporal variation in hotspots by focal species lifestage, habitat and taxonomic family. Results Focal species occurrences and diversity in NZ have increased. We present 17 new‐to‐NZ marine fish species, and a new‐to‐NZ family. Focal species now account for 6.5% of pelagic fishes and 17.3% of benthic fishes in NZ. The northeast of the North Island (Te Ika‐a‐Māui) was a consistent hotspot of focal species occurrences and diversity. Hotspots of mature and pelagic fish occurrences appeared further south than juvenile and benthic species occurrences. Families with tropical affinities (Labridae and Pomacentridae) were restricted to northeastern NZ whereas hotspots of families with temperate affinities (i.e. Cheilodactylidae) extended into the South Island (Te Waipounamu). Main Conclusions Tropical, subtropical and rare fishes are a major component of the fish biodiversity in temperate NZ, and their occurrences and diversity has increased over the past half‐century. Northeastern NZ consistently has the highest occurrence rate and diversity of warmer‐water fishes. Our study demonstrates the value in consolidating citizen scientist observations to detect biodiversity change, and to inform current baselines and future monitoring of climate‐related biodiversity change.

Evidence for short-lived oscillations in the biological records from the sediments of Lago Albano (Central Italy) spanning the period ca. 28 to 17 k yr BP - Piero Guilizzoni; Aldo Marchetto; Andrea Lami; Frank Oldfield; Marina Manca; Claudio A. Belis; Anna M. Nocentini; Patrizia Comoli; Vivienne J. Jones; Steve Juggins; Christina Chondrogianni; Daniel Ariztegui; et al. (Journal of Paleolimnology, 2000)